Solid-state battery unit and solid-state battery

By providing ordered ion channels in the positive electrode, negative electrode and solid electrolyte of the solid-state battery cell, the problem of insufficient ion channel structure in the prior art is solved, and the migration rate of lithium ions and the overall performance of the battery are improved.

CN119400933APending Publication Date: 2025-02-07SICHUAN FULAIWEI NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411740800.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, there are shortcomings in the ion channel structure of the positive electrode sheet, negative electrode materials and solid electrolyte, resulting in low intercalation and discharge efficiency of lithium ions, affecting the charging and discharging performance and cycle life of the battery.

Method used

A solid-state battery cell is designed to ensure the efficiency and order of the ion channel by setting an ordered ion channel in the positive electrode, the negative electrode and the solid electrolyte, and optimize the microstructure to improve the effectiveness of the ion transmission path.

Benefits of technology

By optimizing the ion channel structure, the migration rate of lithium ions is significantly improved, and the charging and discharging rate, cycling stability and energy density of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400933A_ABST
    Figure CN119400933A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of secondary batteries, in particular to a solid-state battery unit and a solid-state battery. The positive electrode unit, the negative electrode unit and the solid electrolyte unit of the solid-state battery unit are elaborately designed and optimized, so that the orderliness and high efficiency of an ion channel are ensured; by optimizing the microstructure, the effective path of ion transmission is increased, rapid intercalation and deintercalation of lithium ions are facilitated, the barrier of ion diffusion is reduced, and the migration rate of the lithium ions is further improved. According to the solid-state battery unit provided by the invention, the ordered ion channels are arranged, so that rapid transmission of metal ions in the battery is realized, and the charge-discharge rate, the cycle stability and the energy density of the battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of secondary batteries, and in particular to a solid-state battery unit and a solid-state battery. Background Art

[0002] With the continuous advancement of secondary battery technology, the combined performance of the positive electrode, negative electrode and solid electrolyte, as the core elements of the battery system, plays a decisive role in the overall performance of the battery. However, in the existing technology, these key components still face a series of challenges, which seriously restricts the improvement of battery performance.

[0003] In terms of positive electrode sheets, although the application of one-dimensional and two-dimensional structured positive electrode active materials has brought new possibilities for improving battery performance, problems such as slow ion diffusion rate and low conductivity remain prominent. These problems limit the efficiency of lithium ion insertion and extraction, which in turn affects the battery's charge and discharge performance and cycle life. In addition, the design and optimization of ion channels in the positive electrode unit are still insufficient, making it difficult to fully meet the needs of high-performance batteries.

[0004] Similarly, negative electrode materials also face challenges such as poor ion transport and limited reaction kinetics. The unreasonable microstructure design of the negative electrode leads to large diffusion barriers of ions in the negative electrode, and the reception and storage capacity of lithium ions is limited, thus affecting the high rate performance and cycle stability of the battery.

[0005] As a key component connecting the positive electrode and the negative electrode, the performance of the solid electrolyte is also crucial. However, the solid electrolytes in the prior art have problems such as poor ion conduction paths and high interface resistance. These problems not only reduce the migration rate of lithium ions, but also affect the safety and stability of the battery. Therefore, the optimization of ion channels in solid electrolytes has become a technical problem that needs to be solved urgently.

[0006] Although the materials with two-dimensional ion channel structures have made significant progress in ion channel design in the prior art, they still face some technical challenges, such as the poor interlayer stability of two-dimensional materials and the inability to precisely control the direction of ion channels.

[0007] In view of the many deficiencies in the ion channel structure of the positive electrode, negative electrode and solid electrolyte in the existing technology, which seriously limit the high-rate charge and discharge capability, cycle stability and energy density of the battery, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention

[0008] The object of the present invention is to provide a solid-state battery cell, which provides a fast transmission path for metal ions by setting up ordered ion channels, thereby reducing the transmission time of ions inside the battery.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions:

[0010] A solid-state battery cell, comprising:

[0011] A positive electrode unit, the positive electrode unit comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer has a first ion channel, and the angle between the first ion channel and the positive electrode current collector is ɑ, and ɑ satisfies the relationship: 0°<ɑ<180°;

[0012] A negative electrode unit, the negative electrode unit comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer has a second ion channel, and an angle β between the second ion channel and the negative electrode current collector is satisfied: 0°<β<180°;

[0013] A solid electrolyte unit, wherein a third ion channel is provided in the solid electrolyte unit, and an angle between the third ion channel and the positive electrode current collector is θ, and θ satisfies the relationship: 0°<θ<180°.

[0014] Preferably, the positive electrode active material layer comprises a sheet-shaped positive electrode active material; the sheet-shaped positive electrode active material is formed by slicing a large-sized positive electrode material of millimeter level or above, and the chemical continuous dimension of the large-sized positive electrode material in at least one direction of three-dimensional space is a, and a satisfies the relationship: a≥0.5mm;

[0015] The negative electrode active material layer includes a sheet-shaped negative electrode active material; the sheet-shaped negative electrode active material is formed by slicing a large-sized negative electrode material of millimeter level or above, and the chemical continuous size of the large-sized negative electrode material in at least one direction of the three-dimensional space is b, and b satisfies the relationship: b≥0.5mm;

[0016] The solid electrolyte unit includes a sheet-like solid electrolyte material; the sheet-like solid electrolyte material is formed by slicing large-size solid electrolyte materials of millimeter level or above, and the chemical continuity dimension of the large-size solid electrolyte material in at least one direction in three-dimensional space is c, and c satisfies the relationship: c≥0.5mm.

[0017] Preferably, the angle between the first ion channel and the positive electrode current collector is ɑ, and ɑ satisfies the relationship: 70°<ɑ<110°;

[0018] The included angle between the second ion channel and the negative electrode current collector is β, and β satisfies the relationship: 70°<β<110°;

[0019] The included angle between the third ion channel and the positive electrode current collector is θ, and θ satisfies the relationship: 70°<θ<110°.

[0020] The positive electrode unit, the negative electrode unit and the solid electrolyte unit are connected by bonding, pressing or sintering.

[0021] Preferably, the chemical size is an atomic-level size or a molecular-level size.

[0022] Preferably, the large-size positive electrode material comprises positive electrode active material particles, and the positive electrode active material particles are positive electrode active materials with a one-dimensional ion channel structure, positive electrode active materials with a two-dimensional ion channel structure, or positive electrode active materials with anisotropic three-dimensional ion channel structures;

[0023] The large-size negative electrode material comprises negative electrode active material particles, wherein the negative electrode active material particles are negative electrode active materials with a one-dimensional ion channel structure, negative electrode active materials with a two-dimensional ion channel structure, or negative electrode active materials with anisotropic three-dimensional ion channel structures;

[0024] The large-size solid electrolyte material comprises solid electrolyte particles, and the solid electrolyte particles are solid electrolyte materials with a one-dimensional ion channel structure, negative electrode active materials with a two-dimensional ion channel structure, or negative electrode active materials with anisotropic three-dimensional ion channel structures.

[0025] Preferably, the first ion channels in the sheet-shaped positive electrode active material are parallel to each other;

[0026] The second ion channels in the sheet-shaped negative electrode active material are parallel to each other;

[0027] The third ion channels in the sheet-like solid electrolyte material are parallel to each other.

[0028] Preferably, the positive electrode current collector comprises one of aluminum foil and composite aluminum foil, and the negative electrode current collector comprises one of copper foil, aluminum foil, composite copper foil and composite aluminum foil.

[0029] The present invention also provides a solid-state battery, comprising the solid-state battery unit mentioned above.

[0030] Preferably, the integrated solid-state batteries are connected in series, in parallel, or in series and parallel.

[0031] The present invention also provides an electrical device, comprising the above-mentioned solid-state battery.

[0032] Compared with the prior art, the beneficial effects of the present invention are as follows: the solid-state battery cell provided by the present invention has been carefully designed and optimized for the positive electrode unit, the negative electrode unit and the solid electrolyte unit to ensure the orderliness and efficiency of the ion channel; by optimizing the microstructure, the effective path of ion transmission is increased, which is conducive to the rapid insertion and extraction of lithium ions, reduces the barrier of ion diffusion, and further improves the migration rate of lithium ions. The solid-state battery cell provided by the present invention realizes the rapid transmission of metal ions inside the battery by setting an orderly ion channel, which significantly improves the charge and discharge rate, cycle stability and energy density of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a cross-sectional view of a solid-state battery cell according to an embodiment of the present invention;

[0034] Figure 2 FIG. 4 is a schematic structural diagram of a positive electrode unit according to an embodiment of the present invention.

[0035] Among them, 1. positive electrode current collector; 2. integrated positive electrode active material unit; 3. integrated solid electrolyte; 4. negative electrode current collector; 5. integrated negative electrode active material unit. DETAILED DESCRIPTION

[0036] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0038] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0039] According to a first aspect of the present invention, a solid-state battery cell comprises:

[0040] A positive electrode unit, the positive electrode unit comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer has a first ion channel, and the angle between the first ion channel and the positive electrode current collector is ɑ, and ɑ satisfies the relationship: 0°<ɑ<180°;

[0041] A negative electrode unit, the negative electrode unit comprises a negative electrode current collector and a negative electrode active material layer arranged on at least one surface of the negative electrode current collector, wherein a second ion channel is provided in the negative electrode active material layer, and an angle β between the second ion channel and the negative electrode current collector is satisfied: 0°<β<180°;

[0042] A solid electrolyte unit, wherein a third ion channel is provided in the solid electrolyte unit, and an angle between the third ion channel and the positive electrode current collector is θ, and θ satisfies the relationship: 0°<θ<180°.

[0043] The solid-state battery cell provided by the present invention has been carefully designed and optimized for the positive electrode unit, the negative electrode unit and the solid electrolyte unit to ensure the orderliness and efficiency of the ion channel; by optimizing the microstructure, the effective path of ion transmission is increased, which is conducive to the rapid insertion and extraction of lithium ions, reduces the barrier of ion diffusion, and further improves the migration rate of lithium ions. The solid-state battery cell provided by the present invention realizes the rapid transmission of metal ions inside the battery by setting an orderly ion channel, which significantly improves the charge and discharge rate, cycle stability and energy density of the battery.

[0044] In one embodiment of the present invention, the positive electrode active material layer includes a sheet-shaped positive electrode active material; the sheet-shaped positive electrode active material is formed by slicing a large-sized positive electrode material of millimeter size or above, and the chemical continuous size of the large-sized positive electrode material in at least one direction of the three-dimensional space is a, and a satisfies the relationship: a≥0.5mm;

[0045] The negative electrode active material layer includes a sheet-shaped negative electrode active material; the sheet-shaped negative electrode active material is formed by slicing a large-sized negative electrode material of millimeter level or above, and the chemical continuous dimension of the large-sized negative electrode material in at least one direction of three-dimensional space is b, and b satisfies the relationship: b≥0.5mm;

[0046] The solid electrolyte unit includes a sheet-like solid electrolyte material; the sheet-like solid electrolyte material is formed by slicing large-size solid electrolyte materials of millimeter level or above, and the chemical continuity dimension of the large-size solid electrolyte material in at least one direction of three-dimensional space is c, and c satisfies the relationship: c≥0.5mm.

[0047] In one embodiment of the present invention, the positive electrode active material layer includes N sheet-shaped positive electrode active materials, wherein N≥1; the N sheet-shaped positive electrode active materials are spread on the positive electrode current collector.

[0048] The negative electrode active material layer includes N sheets of negative electrode active materials, wherein N≥1; the N sheets of negative electrode active materials are spread on the negative electrode current collector.

[0049] The active material layer can be composed of one sheet of active material or two or more sheets of active material. Each sheet of material is cut according to a specific direction of the internal structure to obtain multiple sheet active materials with internal ion channels parallel to each other. There can be gaps between adjacent sheet active materials, or adjacent sheet active materials can be installed closely on the current collector. In summary, these ordered ion channels in the negative electrode active unit provide a fast transmission path for metal ions, reducing the transmission time of ions inside the material.

[0050] In one embodiment of the present invention, the angle between the first ion channel and the positive electrode current collector is ɑ, and ɑ satisfies the relationship: 70°<ɑ<110°; for example, it can be 70°, 71°, 72°, 73°, 74°, 75°, 76°, 77°, 78°, 79°, 80°, 81°, 82°, 83°, 84°, 85°, 86°, 87°, 88°, 89°, 90°, 91°, 92°, 93°, 94°, 95°, 96°, 97°, 98°, 99°, 100°, 101°, 102°, 103°, 104°, 105°, 106°, 107°, 108°, 109°, 110°.

[0051] The angle between the second ion channel and the negative electrode current collector is β, and β satisfies the relationship: 70°<β<110°, for example, it can be 70°, 71°, 72°, 73°, 74°, 75°, 76°, 77°, 78°, 79°, 80°, 81°, 82°, 83°, 84°, 85°, 86°, 87°, 88°, 89°, 90°, 91°, 92°, 93°, 94°, 95°, 96°, 97°, 98°, 99°, 100°, 101°, 102°, 103°, 104°, 105°, 106°, 107°, 108°, 109°, or 110°.

[0052] The angle between the third ion channel and the positive electrode current collector is θ, and θ satisfies the relationship: 70°<θ<110°, for example, it can be 70°, 71°, 72°, 73°, 74°, 75°, 76°, 77°, 78°, 79°, 80°, 81°, 82°, 83°, 84°, 85°, 86°, 87°, 88°, 89°, 90°, 91°, 92°, 93°, 94°, 95°, 96°, 97°, 98°, 99°, 100°, 101°, 102°, 103°, 104°, 105°, 106°, 107°, 108°, 109°, or 110°. When the angle of ion channels is controlled within this range, the ion transmission efficiency can be significantly improved; further, when all ion channels are controlled within this range, even if the ion channels are not parallel to each other, the ion transmission efficiency is very good.

[0053] In one embodiment of the present invention, the positive electrode unit, the negative electrode unit and the solid electrolyte unit are connected by bonding, pressing or sintering.

[0054] In one embodiment of the present invention, the chemical size is an atomic-level size or a molecular-level size.

[0055] In one embodiment of the present invention, the large-size positive electrode material includes positive electrode active material particles, and the positive electrode active material particles are positive electrode active materials with a one-dimensional ion channel structure, positive electrode active materials with a two-dimensional ion channel structure, or positive electrode active materials with anisotropic three-dimensional ion channel structures; when these three materials are used as positive electrode active materials to prepare positive electrode sheets, if the direction of the ion channel is parallel to the positive electrode current collector or many ion channels are arranged chaotically, the ion transmission speed will be seriously reduced, affecting the electrochemical performance of the battery.

[0056] Large-size negative electrode materials include negative electrode active material particles, which are negative electrode active materials with a one-dimensional ion channel structure, negative electrode active materials with a two-dimensional ion channel structure, or negative electrode active materials with anisotropic three-dimensional ion channel structure. When these three materials are used as negative electrode active materials to prepare negative electrode sheets, if the direction of the ion channel is parallel to the negative electrode current collector or many ion channels are arranged chaotically, the ion transmission speed will be seriously reduced, affecting the electrochemical performance of the battery.

[0057] Large-size solid electrolyte materials include solid electrolyte particles, which are solid electrolyte materials with one-dimensional ion channel structures, negative electrode active materials with two-dimensional ion channel structures, or negative electrode active materials with anisotropic three-dimensional ion channel structures. When these three materials are used as solid electrolyte materials to prepare solid electrolyte units, if the direction of the ion channel is parallel to the positive electrode current collector or many ion channels are arranged in a disordered manner, the ion transmission speed will be seriously reduced, affecting the electrochemical performance of the battery.

[0058] In one embodiment of the present invention, the positive electrode active material of the one-dimensional ion channel structure is selected from one of Na2Fe2(SO4)3 and AMPO4, wherein A is at least one of Li and Na, and M is at least one of Fe and Mn; the positive electrode active material of the two-dimensional ion channel structure is selected from MoS2, WS2, MnO2, V2O5, TiN, TiC, Li 1+XV3O8, Li2FeSiO4, Li2MnSiO4 and AMO2, wherein A is at least one of Li, Na, K, and M is at least one of Co, Ni, Mn, ATi, and Cr; the positive electrode active material with anisotropic three-dimensional ion channel structure is selected from spinel structure LiMn2O4, three-dimensional network structure Fe4[Fe(CN)6]3, tetrahedral structure Li2CoSiO4, anti-fluorite structure Li6CoO4, Li3V2(PO4)3 and A x M y (X a Q b ) z Z w , wherein A is at least one of Li, Na, and K, M is at least one of Ti, V, Cr, Mn, Fe, Co, Ni, Ca, Mg, Al, and Nb, X is at least one of Si, S, P, As, B, Mo, W, and Ge, and Z is at least one of F and OH.

[0059] The negative electrode active material of the one-dimensional ion channel structure is carbon nanotubes or single-walled carbon nanotubes; the negative electrode active material of the two-dimensional ion channel structure is graphite, hard carbon, soft carbon, graphene, black phosphorene, Na2Ti3O7, Na 0.66 [Li 0.22 Ti 0.78 ]O2、Na 0.6 [Cr 0.6 Ti 0.4 ]O2, NaTiOPO4, NH4TiOPO4, KTiOPO4, one of two-dimensional metal-based chalcogenides and metal-based oxides; the material with anisotropic three-dimensional ion channel structure is one of silicon-carbon negative electrode material, lithium-carbon negative electrode material, lithium polymer negative electrode material, carbon nanotube wire ball negative electrode material, silicon nanowire ball negative electrode material, germanium nanowire ball negative electrode material, tin nanowire ball negative electrode material and graphene ball negative electrode material.

[0060] Solid electrolyte materials with one-dimensional ion channel structures, such as NASICON solid electrolytes, have a structural formula of NaM(PO4)3, where M is usually a metal element such as Fe, V, and Cr; solid electrolyte materials with two-dimensional ion channel structures, such as LISICON solid electrolytes, have a structural formula of Li 1+x Al x Ge 2-x P3O 12 ; Solid electrolyte materials with anisotropic three-dimensional ion channel structures are mainly selected from the following three types: (1) polymer solid electrolyte materials, such as polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, polyvinyl chloride, polyvinylidene, etc.; (2) sulfide solid electrolyte materials, including sulfur-based fast ion conductor materials Li 4-x A1-γ B γ S4, where A = Ge and Si, etc., B = P, Al and Zn, etc.; Argentum-type solid electrolyte material Li 7-a+b [P,As,Sb] 1-b M b S 6-a-c N c X a , where X = Cl, Br and I; N = O and Se; M = Si; and LGPS-type electrolyte material Li 11- z M 2-z P 1+z S 12 , wherein 0<z<2, m includes any one of Ge, Si, Sn elements; (3) halide solid electrolyte material Li a MX b , where M is a metal element and X is a halogen element. Common halide electrolyte structures include Li a MX4, Li a MX6 and Li a MX8 three categories.

[0061] In one embodiment of the present invention, the first ion channels in the sheet-shaped positive electrode active material are parallel to each other;

[0062] The second ion channels in the sheet-shaped negative electrode active material are parallel to each other;

[0063] The third ion channels in the sheet-like solid electrolyte material are parallel to each other.

[0064] The ion channels in sheet-like positive electrode active materials, sheet-like negative electrode active materials or sheet-like solid electrolyte materials are parallel to each other. This setting has made significant progress in ion channel design because these ordered ion channels provide a fast transmission path for ions, reduce the transmission time of ions inside the material, and improve the efficiency of lithium ion insertion and extraction, thereby optimizing the battery's charge and discharge performance and cycle life.

[0065] The positive electrode current collector includes one of aluminum foil and composite aluminum foil, and the negative electrode current collector includes one of copper foil, aluminum foil, composite copper foil and composite aluminum foil. The current collector is usually a structure or part that collects current, and the current collector can be any material suitable for use as a secondary battery current collector in the art.

[0066] According to a second aspect of the present invention, there is also provided a method for preparing a solid-state battery cell, comprising the following steps:

[0067] Step 1: Forming the positive electrode active material particles into a large-sized positive electrode material of millimeter size or above, and scanning the large-sized positive electrode material with an electron microscope to obtain the internal structure of the large-sized positive electrode material;

[0068] The included angle between the cutting direction and the ion channel of the large-size positive electrode material is ɑ, and ɑ satisfies the relationship: 0≤ɑ≤180°, thereby obtaining a sheet-like positive electrode active material; the sheet-like positive electrode active material is installed on at least one surface of the positive electrode current collector to obtain a positive electrode unit.

[0069] Step 2: Forming the negative electrode active material particles into a large-sized negative electrode material of millimeter size or above, and scanning the large-sized negative electrode material with an electron microscope to obtain the internal structure of the large-sized negative electrode material;

[0070] The included angle between the cutting direction and the ion channel of the large-size negative electrode material is β, and β satisfies the relationship: 0°<β<180°, thereby obtaining a sheet-like negative electrode active material; the sheet-like negative electrode active material is installed on at least one surface of the negative electrode current collector to obtain a positive electrode unit.

[0071] Step 3: forming the solid electrolyte material particles into a large-sized solid electrolyte material of millimeter size or above, and scanning the large-sized solid electrolyte material with an electron microscope to obtain the internal structure of the large-sized solid electrolyte material;

[0072] In one embodiment of the present invention, the angle between the cutting direction and the ion channel of the large-size solid electrolyte material is θ, and θ satisfies the relationship: 0°<θ<180°, thereby obtaining a sheet-like solid electrolyte material; the sheet-like solid electrolyte material is connected to obtain a solid electrolyte unit.

[0073] The internal structure of the large-sized positive electrode material can be obtained by scanning with an electron microscope, or other testing instruments and methods that can obtain the internal structure of the large-sized positive electrode active material can be used.

[0074] In a third aspect of the present invention, a solid-state battery is also provided, comprising the above-mentioned solid-state battery unit.

[0075] The integrated solid-state batteries are connected in series, in parallel, or in series and parallel.

[0076] In a fourth aspect of the present invention, there is also provided an electrical device comprising the above-mentioned solid-state battery.

[0077] Among them, the electrical device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, and an electric tool, etc. The vehicle can be a fuel vehicle, a gas vehicle, or a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, etc.; the spacecraft includes an airplane, a rocket, a space shuttle, and a spacecraft, etc.; the electric toy includes a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc.; the electric tool includes a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and an electric tool for railways, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, etc. The embodiments of the present application do not impose any special restrictions on the above-mentioned electrical devices.

[0078] The embodiments of the present application do not impose any special restrictions on the above-mentioned electrical devices.

[0079] The present invention will be further described below by means of specific examples.

[0080] Example 1

[0081] Preparation of positive electrode unit:

[0082] Step 1: Making LiFePO4 particles into a large-sized positive electrode material of millimeter size or above, and scanning the large-sized positive electrode material with a scanning electron microscope to obtain the internal structure of the large-sized positive electrode material;

[0083] Step 2: The included angle between the cutting direction and the ion channel of the large-sized positive electrode material is 90°, so as to obtain a sheet-shaped positive electrode active material;

[0084] Step 3: Spread a plurality of sheet-like positive electrode active materials on the two surfaces of the current collector to obtain a positive electrode unit; wherein the angle between the ion channel and the positive electrode current collector is 90°.

[0085] Preparation of negative electrode unit:

[0086] Step 1: Making graphite particles into a large-sized negative electrode material of millimeter size or above, and scanning the large-sized negative electrode material with a scanning electron microscope to obtain the internal structure of the large-sized negative electrode material;

[0087] Step 2: The included angle between the cutting direction and the ion channel of the large-sized negative electrode material is 90°, so as to obtain a sheet-shaped negative electrode active material;

[0088] Step 3: Spread a plurality of sheet-like negative electrode active materials on the two surfaces of the current collector to obtain a negative electrode unit; wherein the angle between the ion channel and the negative electrode current collector is 90°.

[0089] Preparation of solid electrolyte:

[0090] Step 1: forming the particles into a large-sized solid electrolyte material of millimeter size or above, scanning the large-sized solid electrolyte material with a scanning electron microscope to obtain the internal structure of the large-sized solid electrolyte material;

[0091] Step 2: The included angle between the cutting direction and the ion channel of the large-sized solid electrolyte material is 90°, so as to obtain a sheet-shaped solid electrolyte material;

[0092] Step 3: Connect multiple sheet-like solid electrolyte active materials to obtain a solid electrolyte unit; wherein the angle between the ion channel and the positive electrode current collector is 90°.

[0093] Preparation of solid-state batteries:

[0094] The positive electrode sheet, solid electrolyte membrane and negative electrode sheet are stacked together to form a "sandwich" structure, and then packaged to obtain a solid-state battery.

[0095] Table 1 shows the experimental parameters of Examples 1 to 15 and Comparative Example 1. The rest are the same as Example 1 and will not be repeated here.

[0096] Table 1

[0097]

[0098]

[0099] Comparative Example 1

[0100] Preparation of negative electrode:

[0101] Graphite, conductive agent carbon nanotubes, binder styrene butadiene rubber, and thickener sodium carboxymethyl cellulose are stirred and mixed in deionized water at a mass ratio of 97.2:1.2:0.8:0.8. After being mixed evenly, the negative electrode slurry is coated on copper foil, baked, rolled, and stripped to obtain a negative electrode sheet.

[0102] Preparation of positive electrode:

[0103] The positive electrode material LiFePO4, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) obtained in the experiment were fully stirred in a N-methyl methyl pyrrolidone solvent system at a mass ratio of 95.5:2.5:2. After being stirred evenly, a positive electrode slurry was obtained, and the slurry was coated on an Al foil, baked, rolled, and cut into strips to obtain a positive electrode sheet.

[0104] Preparation of diaphragm:

[0105] Polyethylene (PE) polymer film is used as the isolation membrane.

[0106] Preparation of electrolyte:

[0107] An organic solution is obtained by mixing the following components and mass ratios: ethylene carbonate (EC): propyl propionate (PP): vinylene carbonate (VC): diethyl carbonate (DEC): propylene carbonate (PC) = 22:25:3:28:22; lithium salt LiPF6 is added to the organic solution, and the mass ratio of the added mass to the organic solution is 9.5:90.5; after mixing evenly, an electrolyte is obtained.

[0108] Preparation of the battery:

[0109] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order and wound to obtain an electrode assembly; the electrode assembly is placed in a packaging shell, an electrolyte is injected into the packaging shell and the packaging is performed to finally obtain a lithium-ion battery.

[0110] Performance Testing:

[0111] The secondary batteries of Examples 1 to 15 and Comparative Example 1 were subjected to a DC internal resistance test and a charge and discharge test. The results are shown in Table 2.

[0112] Table 2

[0113]

[0114]

[0115] As can be seen from Table 2, by comparing the experimental data of Examples 1 to 15 with that of Comparative Example 1, it can be seen that the time data of 5C charging to 80% power and the discharge rate data of the battery 1.0C@0.2C of Examples 1 to 15 are better than those of Comparative Example 1, indicating that the ordered ion channels provided in the present invention can provide a fast transmission path for ions, reduce the transmission time of ions inside the material, improve the efficiency of lithium ion embedding and extraction, and thus optimize the charge and discharge performance and cycle life of the battery.

[0116] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A solid-state battery cell, characterized in that: include: A positive electrode unit, the positive electrode unit comprising a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer has a first ion channel, and the angle between the first ion channel and the positive electrode current collector is ɑ, and ɑ satisfies the relationship: 0°<ɑ<180°; A negative electrode unit, the negative electrode unit comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer has a second ion channel, and an angle β between the second ion channel and the negative electrode current collector is satisfied: 0°<β<180°; A solid electrolyte unit, wherein a third ion channel is provided in the solid electrolyte unit, and an angle between the third ion channel and the positive electrode current collector is θ, and θ satisfies the relationship: 0°<θ<180°.

2. The solid-state battery cell according to claim 1, characterized in that: The positive electrode active material layer includes a sheet-shaped positive electrode active material; the sheet-shaped positive electrode active material is formed by slicing a large-sized positive electrode material of millimeter level or above, and the chemical continuous size of the large-sized positive electrode material in at least one direction of the three-dimensional space is a, and a satisfies the relationship: a≥0.5mm; The negative electrode active material layer includes a sheet-shaped negative electrode active material; the sheet-shaped negative electrode active material is formed by slicing a large-sized negative electrode material of millimeter level or above, and the chemical continuous size of the large-sized negative electrode material in at least one direction of the three-dimensional space is b, and b satisfies the relationship: b≥0.5mm; The solid electrolyte unit includes a sheet-like solid electrolyte material; the sheet-like solid electrolyte material is formed by slicing a large-size solid electrolyte material of millimeter level or above, and the chemical continuous size of the large-size solid electrolyte material in at least one direction of the three-dimensional space is c, and c satisfies the relationship: c≥0.5mm.

3. The solid-state battery cell according to claim 1, characterized in that: The angle between the first ion channel and the positive electrode current collector is ɑ, and ɑ satisfies the relationship: 70°<ɑ<110°; The included angle between the second ion channel and the negative electrode current collector is β, and β satisfies the relationship: 70°<β<110°; The included angle between the third ion channel and the positive electrode current collector is θ, and θ satisfies the relationship: 70°<θ<110°.

4. The solid-state battery cell according to claim 1, characterized in that: The positive electrode unit, the negative electrode unit and the solid electrolyte unit are connected by bonding, pressing or sintering.

5. The solid-state battery cell according to claim 2, characterized in that: The chemical size is an atomic-level size or a molecular-level size.

6. The solid-state battery cell according to claim 1, characterized in that: The large-size positive electrode material comprises positive electrode active material particles, wherein the positive electrode active material particles are positive electrode active materials with a one-dimensional ion channel structure, positive electrode active materials with a two-dimensional ion channel structure, or positive electrode active materials with anisotropic three-dimensional ion channel structures; The large-size negative electrode material comprises negative electrode active material particles, wherein the negative electrode active material particles are negative electrode active materials with a one-dimensional ion channel structure, negative electrode active materials with a two-dimensional ion channel structure, or negative electrode active materials with anisotropic three-dimensional ion channel structures; The large-size solid electrolyte material comprises solid electrolyte particles, and the solid electrolyte particles are solid electrolyte materials with a one-dimensional ion channel structure, negative electrode active materials with a two-dimensional ion channel structure, or negative electrode active materials with anisotropic three-dimensional ion channel structures.

7. The solid-state battery cell according to claim 1, characterized in that: The first ion channels in the sheet-shaped positive electrode active material are parallel to each other; The second ion channels in the sheet-shaped negative electrode active material are parallel to each other; The third ion channels in the sheet-like solid electrolyte material are parallel to each other.

8. The solid-state battery cell according to claim 1, characterized in that: The positive electrode current collector includes one of aluminum foil and composite aluminum foil, and the negative electrode current collector includes one of copper foil, aluminum foil, composite copper foil and composite aluminum foil.

9. A solid-state battery, characterized in that: Comprising at least one solid-state battery cell according to any one of claims 1 to 8.

10. The integrated solid-state battery according to claim 9, characterized in that: The integrated solid-state batteries are connected in series, in parallel or in series and in parallel.